166k views
2 votes
Please help me, if you help then thanks!

Please help me, if you help then thanks!-example-1
User HarryM
by
5.3k points

1 Answer

2 votes

Answer:


{x}^(2) {y}^(8) (second option)

Explanation:


\frac{( {x}^(2) {y}^(3) {)}^(4) }{( {x}^(3) {y}^(2) {)}^(2) }


( {x}^(2) {y}^(3) {)}^(4) = ( {x}^(2) {)}^(4) * ( {y}^(3) {)}^(4)


{x}^(8) * ( {y}^(3) {)}^(4) = {x}^(8) {y}^(12)


\frac{ {x}^(8) {y}^(12) }{( {x}^(3) {y}^(2) {)}^(2) } = \frac{ {x}^(8) {y}^(12) }{ {x}^(6) {y}^(4) }


\frac{ {x}^(2) {y}^(12) }{ {y}^(4) } = {x}^(2) {y}^(8)


= {x}^(2) {y}^(8)

User Kahbazi
by
5.1k points